Y Web-Based Academic Information System Design at Praktisi Polytechnic - Yudhi Yanuar; Ari Waluyo (Jurnal E-Komtek, 2022)
This study aims to design an academic information system. The method used in this study uses observation on the object of research and answers. It conducts an assessment of the literature while for the description of the information system using an object-oriented depiction method with UML tools. The waterfall is used as a software development method. The PHP programming language is a programming language and database Mysql. Based tests on academic information systems at practitioner polytechnics can be used properly and effectively, making it easier for users to carry out academic administrative processing.